SAWOHAN-SMART MARITIME VILLAGE (S-SMV): PEMBERDAYAAN MASYARAKAT PESISIR DESA SAWOHAN SIDOARJO UNTUK MENGOPTIMALKAN POTENSI BANDENG DENGAN PAKAN MANDIRI HASIL BUDIDAYA MAGGOT BSF - Cahyo Febri; Lutfi Bayu Indarto; Kharisma Zuliatin Nisak; Fenty Regita Indah Sari; Sekar Nur Hasanah; Akhya Samsa Mardika; Anik Kurnia Ningsih; Sofia Nur Fazira; Marwa Rabitha Rahmaniyah; Maurent Maulidina Masitha; Indana Zulfa; Ellena Ihza Katerina; Mohammad Syahidul Haq (Program Studi S1, S2, S3 Mananajemen Pendidikan Universitas Negeri Surabaya, 2022)
This article is structured with four objectives, namely: (1) to describe how to cultivate and utilize BSF maggots; (2) describe how to optimize the potential of milkfish as a local product; (3) describe the influence of the program on people's income; and (4) describe how to establish and develop the quality of local fishery institutions. The method of implementing KDP consists of the preparation stage, implementation stage, monitoring and evaluation, workshops and hearings, as well as program sustainability. The results of the service that have been carried out are the cultivation and utilization of BSF maggots, starting with socialization and cultivation training with ecologists and continued with the practice of making cages, hatching eggs, and care. Furthermore, training and assistance were also carried out on how to process and market processed milkfish products into nuggets with culinary practitioners. Based on the calculation results, the program has a significant influence on people's income, where the target community who originally did not work becomes an income or it can be said that their income increases by 100%. Then, a local fishery institution was formed consisting of village youths who were tasked with maintaining the consistency of program implementation so that it had a sustainable impact.